Filsafat Ilmu Teologi dalam Era Digital - Agustina Hutagalung (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
This article examines the impact of the digital era on theological methodology through the lens of the philosophy of science. Utilizing a qualitative-descriptive approach based on literature review, the study explores the relationship between theological epistemology and the development of information technology. The article asserts that the philosophy of science plays a crucial role in reinforcing the methodological foundations of theology to address challenges of the digital era, such as information plurality, authority crises, and the simplification of truth. Furthermore, the study provides strategic recommendations for reconstructing theological methods by critically, innovatively, and responsibly leveraging digital technology.